A high-performance calcite-type strontium vanadate hydrate anode enabled by synergistic engineering for fast lithium storage - Xiaolei Li; Jinchi Hou; Zhao Li; Jing Zhang; Xuguang An; Weitang Yao; Qingquan Kong (Chemical Engineering Journal, 2026)

Root exudates recruit microbial allies to override their own mobilization effects for cadmium immobilization in intercropped rice - Ye Li; Jie Hou; Mengqi Liu; Hongan Chen; Xinyi Wang; Peizhe Sun; Lin Zhao; Yanpo Yao; Zhaolin Du; Yi An (Journal of Hazardous Materials, 2026)

A study on SIREN wavefield simulation guided by frequency progressive curriculum - Daoxuan Li; Zhen'an Yao; Cong Chen; Jinbu Hou; Xiangteng Wang (Journal of Applied Geophysics, 2026)

Food-derived bioactive peptides for mitigating sleep architecture disruption and Alzheimer’s disease: Advancements in mechanisms, structure-activity relationships, and evidence gaps - Shumeng Liu; Jiulong An; Wanlu Liu; Shenghong Yao; Saiya Hou; Manqun Wang; Zhiwei Ying; Xinqi Liu; He Li (Food Bioscience, 2026)

Antibiotic resistance genes (ARGs) in rice: Source attribution and putative mobility patterns - Jie Hou; Ye Li; Mengqi Liu; Linyun Li; Hongan Chen; Yi An; Han Xu; Yanpo Yao (Food Microbiology, 2026)

Lanthanum hydroxide modified magnetic bone biochar for enhanced phosphate removal: Performance and mechanism exploration - Hongxuan Chu; Mengning Wang; Qiwen An; Kaitian Zhang; Wenzhen Li; Yuxin Hou; Jiaxin Liu; Jianhua Qu; Ying Zhang (Bioresource Technology, 2026)

Precipitation legacy overrides grazing and nitrogen inputs as the primary driver of interannual soil nitrogen cycling in a semi-arid grassland - Zhen Wang; Mengyuan Wang; Xiumin Zhang; Junqi Hu; Lan Li; An Hu; Xianjiang Chen; Shenghua Chang; Fujiang Hou (Agriculture, Ecosystems & Environment, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Toddacoumalins A-J, ten undescribed coumarins from the roots of Toddalia asiatica - Feng Wu; Han Yao; Xin-Rui Liao; Nan An; Xing-Shu Li; Wen-Hao Hu; Albert S.C. Chan; Hou-Jin Li; Wen-Jian Lan (Phytochemistry, 2026)

Mechanisms of water-state transition and hydrophobicity evolution of organics during ultrasonic dewatering of algal sludge - Shumin Yang; Li-an Hou; Rongsheng Ning; Xinyuan Yi; Shuili Yu; Yulin Tang (Environmental Research, 2026)

Optimizing anaerobic Co-digestion of antibiotic fermentation residue and sludge with iron nanoparticles: Impacts on methane production, microbial dynamics, and biocompatibility - Qianqian Zhang; Yu Yang; Li-an Hou; Nigel J. D. Graham; Yaobin Zhang; How Yong Ng (ENGINEERING Environment, 2026)

Synergistic remediation of saline-alkali soil using a designed microbial consortium H6 with biochar and humic acid - Ting Wei; Maomao Jiang; Rongyi Hu; Yi Zhao; Peiqi Wang; Chaowei Tian; Li Hua; Xueyan Hou; Fengqiu An; Junkang Guo (Journal of Soils and Sediments, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Assessing humus to predict soil organic carbon in Northwest China: A case study of Ningxia - Xinnian GUO; Zhuonan HOU; Xia WU; Huaiyu LONG; Zehua XU; Baiyun LI; Shaoshan AN (Pedosphere, 2026)

Bimetallic catalytic ceramic membrane for sustained water purification: Role of Cu in stabilizing reduced Co centers - Jiaqi Yang; Kexuan Gao; Yiran Chai; Nigel J.D. Graham; Li-an Hou; Yu Yang (Chemical Engineering Journal, 2026)

GDSL lipase complex ZmMS30/IPE2 coordinates fatty acid and phenylpropanoid metabolism to ensure exine foot layer formation in maize - Quancan Hou; Jinghua Niu; Shuangshuang Liu; Juan Zhang; Zhiwei Shui; Zhixian Xu; Ziwen Li; Lina Zhao; Xiaofeng Xue; Xueli An; Huabang Chen; Xiangyuan Wan (Science Bulletin, 2026)

ZmSWEET6A/6B are required for maize male fertility via balancing sugar and lipid metabolism during pollen and anther development - Shuangshuang Liu; Yilin Jiang; Canfang Niu; Fan Zhang; Lina Zhao; Quancan Hou; Ziwen Li; Yingwei Qu; Bin Ma; Qingping Jiang; Yan Long; Xueli An; et al. (Science Bulletin, 2026)

Photocatalytic degradation of indoor mixed VOCs: A mini review on polar and non-polar compounds - Yingni Feng; Jun Wang; Wenjun Wang; Qian Li; Miaomiao Qu; Yun Shi; Jian meng Chen; Mei Zhang; Li’an Hou (Journal of Environmental Sciences, 2026)

Hydroxylamine enhances the iron double-cycle system to improve the removal efficiency of norfloxacin via Fe3O4@N-rGO/PMS system - Lingzi Fu; Chao Wang; Aiguo Lin; Zhangbin Pan; Bin Wang; Li'’an Hou (Chemical Engineering Journal, 2026)

Synergistic coupling of ultrasonic activation and BaTiO3 piezoelectric ceramic membranes for robust algae-water separation: Dynamics of foulant migration and radical oxidation - Shumin Yang; Li-an Hou; Xinyuan Yi; Yongjie Huang; Qianli Zhang; Shuili Yu; Yulin Tang (Journal of Environmental Chemical Engineering, 2026)

Magnetic biochar- loaded nano zero-valent iron for heavy metal passivation: Coupled interaction mechanism between arsenic and cadmium - Yi Hu; Huanhuan An; Xinquan Wei; Ting Liu; Xiao Tang; Li Hua; Dongmei Hou; Xiao Xiao; Xubiao Luo (Journal of Environmental Chemical Engineering, 2026)

Structural advantages of [B8O10(OH)6] for sustainable dual-functional scale/corrosion Inhibition in circulating water systems - Dong Guo; Ruidi Sun; Yahui Zhao; Yuansheng Pei; Li'an Hou (Desalination, 2026)

Clinical application of MALDI-TOF MS for direct and rapid pathogen identification: a comprehensive review focusing on bloodstream infections and sterile body fluids - Chen Peng; Jie Hou; Xin Li; Ao Deng; Ze-Hao Wang; Xue-An Wang; Bin Yang; Li-Sha Luo (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Construction and application of a high-resolution pollen numerical model system based on phenology and XGBoost - Jiangtao Li; Xingqin An; Zhe Liu; Fan Zhao; Huaerqi Huang; Qing Hou; Yu Wang (Environmental Pollution, 2026)

Role of Microglial Dysfunction in Parkinson’s Disease: From Multifactorial Causes to Neurodegeneration - Yuxiang Xu; Tingting Han; Yue Wu; Haixuan Liu; Keyuan Hou; Zhaowu An; Yongjie Li; Chaoyang Zhu; Song Wang; Jianshe Wei (Neuroscience Bulletin, 2026)

A persistently active fast radio burst source embedded in an expanding supernova remnant - Chen-Hui Niu; Di Li; Yuan-Pei Yang; Yuhao Zhu; Yongkun Zhang; Jia-Heng Zhang; Zexin Du; Jumei Yao; Xiaoping Zheng; Pei Wang; Yi Feng; Bing Zhang; et al. (Science Bulletin, 2026)

Pathogen-induced H2O2 triggers phosphorylation of the RNA-binding protein RRM2R to suppress OsMAPKKK18 intron retention for orchestrating rice immunity and growth - Xiang Lu; Yibang An; Wenxiu Lu; Jing Li; Qing Xiong; Miaomiao Zhu; Yao He; Jia Yang; Yue Wang; Zeming Zhang; Xiaorong Gong; Yulong Qian; et al. (Molecular Plant, 2026)

Rational design and synergistic optimization of 2D COF nanofiltration membranes: A review - Tianqi Jia; Zhao Zheng; Leilei Hou; Zhixiang Li; Xueqing Ma; Xinru An; Xia Zhan (Journal of Environmental Chemical Engineering, 2025)

Multiomics and machine learning unveil root exudate-microbiota interactions for cadmium control in rice - Ye Li; Jie Hou; Mengqi Liu; Zhaolin Du; Hongan Chen; Guofei Liu; Yajun Wang; Yanpo Yao; Peizhe Sun; Lin Zhao; Yi An (Journal of Environmental Management, 2025)

Tan sheep excrement type and supply level can alter community parameters through population transformation in a typical steppe - Gulraiz Ahmad; Jing Zhang; Adnan Arshad; An Hu; Lan Li; Shree P. Pandey; Fujiang Hou (Journal of Environmental Management, 2025)

Preparation of CrMnTi catalysts and mechanistic study on their photothermal synergistic degradation of toluene - Dan Zhang; Ziyi Jing; Li'an Hou; Fahui Wang; Anchao Zhang; Yonghui Li; Shuxian Yin; Tao Han (Journal of Environmental Chemical Engineering, 2025)

Dietary Supplementation with Multi-strain Probiotic Formulation (Bifidobacterium B8101, Lactobacillus L8603, Saccharomyces bayanus S9308, and Enterococcus SF9301), Betaine or their Combination Promotes Growth Performance Via Improving Intestinal Development in Broilers - Dan Hu; Xiaoting Wu; Pin Song; Manman Hou; Li’an Pan; Xiaoran Yang; Qinwei Sun; Yingdong Ni (Probiotics and Antimicrobial Proteins, 2025)

A CSDG photoelectronic transistor based on simulation model mimicking dopamine-facilitated synaptic plasticity for high energy-efficient neuromorphic system - Qing-an Ding; Yuhua Gao; Chunyan Liu; Chaoran Gu; Xiaoyuan Li; Fangfang Ning; Binghui Hou; Yandong Peng; Bing Chen (Cognitive Neurodynamics, 2025)

Synergistic effect of two complementary acceptors assists high-efficiency as-cast organic solar cells - Mengyun Jiang; Bao Zhang; Peng Mao; Qian Guo; Yingqi Wang; Jiawei Qiao; Tao Zhang; Yongmin Luo; Quansong Li; Xiaotao Hao; Jianhui Hou; Jiaying Wu; et al. (Science Bulletin, 2025)

Identification and functional characterization of Cyprinus carpio cGAS reveals its pivotal role against viral infection - Chun Li; Guoli Hou; Liang Hu; Yang Xu; Qiushi Zhang; Xinyu Liang; Yong-An Zhang; Junhua Li (Fish & Shellfish Immunology, 2025)

Time-series transcriptomic analysis reveals survival strategies of dominant strains in a domesticated community and their influence on polyhydroxyalkanoates synthesis in co-culture - Lingyi Hou; Boya Liang; Fanzhe Chang; Fang Wang; Shankui Liu; Peng Zhang; Liyun An; Qiang Li (Bioresource Technology, 2025)

A machine learning and counterfactual reasoning-integrated decision framework for cadmium remediation: Predictive optimization and cost-benefit analysis driven by iron plaque regulation - Ye Li; Jie Hou; Mengqi Liu; Ruilin Li; Zhaolin Du; Yanpo Yao; Peizhe Sun; Lin Zhao; Yi An (Journal of Hazardous Materials, 2025)

Constructing S/N-vacancy-and Co/Mo-bimetallic-catalysts for tetracycline degradation through peroxymonosulfate activation: evolution of active substance - Jiaqi Yang; Yu Yang; Kexuan Gao; Nigel J.D. Graham; Li-an Hou (Environmental Research, 2025)

Impact of boron hybridization types on polyborates scale inhibition in circulating water systems - Dong Guo; Haixu Hou; Yuansheng Pei; Li'an Hou (Desalination, 2025)

Insight into transformation of phosphorus species in biomass gasification at different stages - Xuemei Fu; Beibei Yan; Jian Li; Yanshan Wang; Xiaoqiang Cui; Guanyi Chen; Wenzhu Wu; Li’an Hou (Bioresource Technology, 2025)

Mesenchymal Stem Cells Derived from Different Adipose Tissue Depots Ameliorate Severe Acute Pancreatitis by Inhibiting NF-κB/NLRP3/Caspase-1 Pathways - Ao Wang; Yu An; Xuefei Wang; Wenfeng Gou; Feifei Xu; Yanli Li; Cong Wang; Zhengwei Tu; Wenbin Hou; Yunfeng Cui (Stem Cell Reviews and Reports, 2025)

Plant community‐dominating species can sustain population biomass by modifying and strengthening their own growth traits to deal with long‐term grazing - Yu-Wen Zhang; Ze-Chen Peng; Zhao-Feng Wang; Sheng-Hua Chang; Yu-Feng An; Duo-Cai Li; Fu-Jiang Hou; Ji-Zhou Ren (Agriculture, Ecosystems & Environment, 2025)

Machine learning and network toxicology reveal arsenic as a key driver of non-carcinogenic health risks from heavy metal residues in Chinese medicinal plants - Guangying Du; Yuanju Zhang; Ting Zou; Chang Liu; Yingyue Hou; Jing Li; Feifei Deng; Jiayi An; Li Feng; Bangna Wu; Lingdan Huang; Ying Zhou (Science of The Total Environment, 2025)

Transmembrane uptake of polystyrene nanoplastics mediated by aquaporin in tartary buckwheat: Physiological consequence and genomic mechanism - Yu-Kang Hou; Shuo Gao; Qiang Lai; Wen-Rui Lu; You-Bao Cai; Ya-Wen Yuan; Si-Yuan Yao; Hong-Yan Tao; Li-Zhe An; You-Cai Xiong; Yuan Song (Journal of Hazardous Materials, 2025)

Tea polyphenols attenuate glufosinate-induced breast injury by reducing endoplasmic reticulum stress and autophagy - Fu Li; Zhanhang Wang; Muhua Luo; Jiaxiang Hu; Haifeng Wang; Yonglong He; Danni Li; Yuan Yuan; Jinxing Hou; Yuxuan Song; Lei Zhang; Binyun Cao; et al. (Journal of Hazardous Materials, 2025)

Engineering oxygen vacancies and acidic site density in MnOx/CMS via Mn3+/Mn4+ ratio manipulation for ambient deep desulfurization - Huirong Zhang; Wenyue Wang; Xiaotong Chang; Li-an Hou; Yi Wei; Bo Wang; Yun Zhang (Journal of Cleaner Production, 2025)

Novel 3D porous mycelium membrane fabricated using controllable self-growth strategy for self-cleaning and multifunctional water purification - Xia Fang; Junkai Gao; Mengsheng Xia; Jingyuan Ren; Yongqi Chen; Yan Chen; Li'an Hou (Journal of Cleaner Production, 2025)

Multi-step ahead probabilistic runoff forecasting with SHAP interpretability: a GPR-enhanced deep learning ensemble approach integrating teleconnection factors - Feilin Zhu; Tiantian Hou; Ou Zhu; Yitong Sun; Weifeng Liu; Lingqi Zhao; Xuning Guo; Min Li; Ping-an Zhong (Environmental Modelling & Software, 2025)

ZmMS1-orchestrated feedback repression loop regulates ZmACSN2/3—PKSB—TKPR1-1/-2 complex to ensure maize pollen development - Xueli An; Chaowei Fang; Shaowei Zhang; Yilin Jiang; Xiaofeng Xue; Quancan Hou; Lina Zhao; Ziwen Li; Xiangyuan Wan (Science Bulletin, 2025)

A reconstruction of Antarctic Sea ice extent since the 1950s from a snowpit methanesulfonate (MSA) record in East Antarctic inland - Jinhai Yu; Hongxi Pang; Guitao Shi; Wangbin Zhang; Shuangye Wu; Chunlei An; Yuansheng Li; Shugui Hou (Journal of Marine Systems, 2025)

Single-atom Zn anchored on reduced graphene oxide for enhanced peroxymonosulfate activation: Critical role of Zn-O3 coordination structure and catalytic mechanism - Yinhua Wang; Chengsheng Ni; Qing Yang; Junfeng Niu; Lilan Zhang; Li-an Hou; Chong Wang (Journal of Hazardous Materials, 2025)

Changes in soil organic carbon and its forms in recovering alpine meadows of various lengths in relation to altitude - Chunying Lin; Xilai Li; Huafang Sun; Xiaoxue Su; Hongmei Li; Rongna Liu; Chengyi Li; Yonghui Hou; Shizhen Zhu; Di Yu; Liyan Zhang; Jiexia Li; et al. (CATENA, 2025)

Grazing overrides precipitation reduction to regulate growth of a dominant species in a typical steppe - Liyuan Shi; Zhen Wang; Xiong Z. He; Lan Li; An Hu; Fujiang Hou (Agriculture, Ecosystems & Environment, 2025)

Fate and behavior of uranium biomineralization by the native Burkholderia sp. S1 isolated from tailing areas - Jun He; Yubin Hong; Yihang Zhao; Xinyu Hong; Xinye Cheng; Yongjian Xie; Qingqing Xiao; Wanrou Liu; Lihua Dong; Li’an Hou; Diyun Chen (Journal of Environmental Chemical Engineering, 2025)

Nano silicon causes a shift in rhizospheric soil microbial community structure and improves nutrient uptake and assimilation in tomato plants under low temperature - Yu Shi; Lu An; Shuxun Guo; Jieyu Li; Huixian Sun; Ruixing Zhang; Hailiang Zhao; Longqiang Bai; Leiping Hou; Yi Zhang; Golam Jalal Ahammed (Soil and Tillage Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Identification and functional analysis of mitochondrial protein-coding genes associated with the adaptability to cold stress of the rusty grain beetle Cryptolestes ferrugineus - Guo-Qing Yuan; Meng-Qiu Chen; Qiu-Li Hou; Pei-An Tang; Er-Hu Chen (Journal of Stored Products Research, 2025)

Modelling reactive transport of metals in Wujiang cascade reservoirs under coal-fired, hydro power generation and fishing ban scenarios - Qingqing Sun; Bowen Zhou; Jingfu Wang; Jing-An Chen; Pan Ni; Narek Galustanian; Jingyi Hou; Chunyi Wang; Si-Liang Li (Journal of Hazardous Materials, 2025)

Selective removal of mercury ions from aqueous solution by thiourea-functionalized porous aromatic framework - Zi-Xuan Jin; He-Jie Lu; Xiang-Wen Chen; Yi-Hang Li; Si-Chao Zhu; Xiu-Lei Li; Zhi-Qian Jia; Yuexin Guo; Yu Yang; Li-An Hou (Desalination, 2025)

PM2.5-bound polycyclic aromatic hydrocarbons (PAHs) in urban Beijing during heating season: Hourly variations, sources, and health risks - Yu Wang; Zhaojin An; Youhua Zhao; Hao Yu; Dongbin Wang; Guodong Hou; Yuke Cui; Wuyue Luo; Qianhe Dong; Pengtuan Hu; Leicheng Zhao; Zhiguo Cao; et al. (Atmospheric Environment, 2025)

Storm deposit characteristics and orbital cyclicity of the Early Devonian Xiejiawan Formation in the Longmenshan area, Sichuan Province, China - Fengjie Li; Zheng’an Chen; Sanem Acikalin; James G. Ogg; Shannon Flynn; Gengchuan Liu; Pengfei Zhang; Jia Wang; Anqing Chen; Mingcai Hou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Odor impact patterns and health risks of various enterprises in the rubber product manufacturing industry - Yan Zhang; Yan Zhao; Li’an Hou; Zhiyang Zhang; Kehua Zou; Gen Wang; Zhiqiang Lu; Huanwen Cui; Jie Meng; Ting Wu; Jing Wang; Zengxiu Zhai (Journal of Hazardous Materials, 2025)

Simulation investigation on separation characteristics of gas-liquid model products from in-situ pyrolysis of tar-rich coal - Tianlin Yuan; Chang’an Wang; Meijing Chen; Fu Yang; Yujie Hou; Li Ma; Zhonghui Duan; Defu Che (Journal of Environmental Chemical Engineering, 2025)

A review of antibiotic resistance genes in major river basins in China: Distribution, drivers, and risk - Wenjia Li; Bin Wang; Tao Wang; Jiang Li; Junmin Qi; Jiwei Luo; Ting Zhang; Xiaoyi Xu; Li'an Hou (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

In vivo self-assembled bispecific fluorescence probe for early detection of bladder cancer and metastasis - Da-Yong Hou; Ni-Yuan Zhang; Peng Zhang; Xiang-Peng Li; Jiong-Cheng Wu; Mei-Yu Lv; Zhi-Jia Wang; Xing-Jie Hu; Jian-Xiao Liang; Hong-Lei Wang; Yue-Ze Wang; Hui-Hui You; et al. (Science Bulletin, 2025)

Unraveling the role of V modified CoO in a wide pH range Fenton-like process - Xiaoyi Huang; Qiangqiang Wu; Jingwen Tang; Rongsheng Ning; Jiang Yuan; Shengqiong Fang; Shuili Yu; Li'an Hou; Qinglun You (Journal of Environmental Management, 2025)

Metagenomics reveals the resistance patterns of electrochemically treated erythromycin fermentation residue - Jieya Zhou; Hao Wu; Haiyan Wang; Zongru Wu; Lihu Shi; Shulei Tian; Li-an Hou (Journal of Environmental Sciences, 2025)

Isolation and evaluation of growth-promoting endophytic bacteria from Zanthoxylum dissitum Hemsl. - Lingyu Fei; Ziying Hou; Yuan Wang; Jikang Sun; Tingting An; Qiuyun Li (Physiology and Molecular Biology of Plants, 2025)

Significant effects of bioavailable heavy metals on antibiotic resistome in paddy soils as revealed by metagenomic analysis - Jie Hou; Ye Li; Mengqi Liu; Zheng Qu; Zhaolin Du; Yi An; Fengxia Yang; Yanpo Yao (Journal of Hazardous Materials, 2025)

Pattern recognition of multiple metal ions using fluorescent Perylenyl nanoaggregates and application in food traceability - Tianyue Liu; Yining Li; He Cheng; Ruixuan An; Xinglin Hou; Yasong Zhang; Jieyu Zhao; Hao Zhang; Jingsheng Tian; Zhiyi Yao (Food Chemistry, 2025)

Fast complete reduction of chlorite to chloride from drinking water in Al(III)/sulfite system: Kinetics, mechanisms, and applications - Xingli Ji; Li-an Hou; Shuili Yu; Ying Xu; Menghong Gao; Wei Zhang; Qian Xiao (Chemical Engineering Journal, 2025)

Digital electronics-free implantable drug delivery system for on-demand therapy - Jiarong Hu; Jingbo Zhang; Yufei Hou; Congsun Li; Weinan Yang; Jianzhong Fu; Songyu Hu; An Liu; Yong He (Chemical Engineering Journal, 2025)

Novel catalyst-free activation of chlorine by visible light for micropollutant abatement - Ge Zeng; Linqian An; Maoju Jiang; Wenqi Li; Xiangyang Hou; Peng Su; Minchao Liu; Haijun Cheng; Zhiyun Long; Jingxin Yang; Jun Ma; Tao Yang (Journal of Hazardous Materials, 2024)

Chronic PM2.5 exposure disrupts intestinal barrier integrity via microbial dysbiosis-triggered TLR2/5-MyD88-NLRP3 inflammasome activation - Zihan Ran; Jingcheng Yang; Liang Liu; Shaobo Wu; YanPeng An; Wanwan Hou; Tianyuan Cheng; Youyi Zhang; Yiqing Zhang; Yechao Huang; Qianyue Zhang; Jiaping Wan; et al. (Environmental Research, 2024)

Large-area and high-efficiency carbon nanotube/silicon heterojunction solar cells enabled by self-similar fiber electrodes and solid-state gel electrolytes - Xian-Gang Hu; Bingsheng Li; Yi-Ming Zhao; An-Ping Wu; Zhenhua Lin; Peng-Xiang Hou; Chang Liu; Yue Hao; Jingjing Chang (Chemical Engineering Journal, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

Flow-Slip Stability Behavior of Calcareous Sand Treated by Microbially Induced Carbonate Precipitation Technology - Hailei Kou; Xiang He; Wangxiang Hou; Zhendong Li; Xixin Zhang; Zhaotun An; Jiaqing Lu (Journal of Ocean University of China, 2024)

Indirect photodegradation of typical pyrrolizidine alkaloids in water induced by triplet states of dissolved organic matter - Menghong Gao; Shuili Yu; Rongsheng Ning; Xingli Ji; Ying Xu; Li’an Hou (Journal of Hazardous Materials, 2024)

Fouling behavior of BTEX in petrochemical wastewater treated by nanofiltration (NF) - Kexuan Gao; Yu Yang; Ao Li; Jian Pu; Satoshi Takizawa; Nigel J.D. Graham; Li-an Hou (Journal of Hazardous Materials, 2024)

Concurrent and legacy effects of sheep trampling on soil organic carbon stocks in a typical steppe, China - Lan Li; Xiong Zhao He; Jing Zhang; Racheal Bryant; An Hu; Fujiang Hou (Journal of Environmental Management, 2024)

Activation preference: A new descriptor to predict non-radical oxidation pathways - Lan Liang; Ning Li; Zhixun Li; Zhanjun Cheng; Beibei Yan; Guanyi Chen; Li-an Hou (Chemical Engineering Journal, 2024)

Self-assembled membrane with excellent antifouling performance for enhanced treatment of petrochemical wastewater - Kexuan Gao; Yu Yang; Nigel J.D. Graham; Ying Zhang; Yilin Jiang; Cheng Duan; Ao Li; Qianqian Zhang; Xiaoqiang An; Li-an Hou (Chemical Engineering Journal, 2024)

Ionic complexation, metal coordination, and physiological stress effects of polyborate - Dong Guo; Haixu Hou; Xiaohuan Yang; Yuansheng Pei; Li'an Hou (Desalination, 2024)

Photo-assisted natural chalcopyrite activated peracetic acid for efficient micropollutant degradation - Linqian An; Xiujuan Kong; Maoju Jiang; Wenqi Li; Qixiao Lv; Xiangyang Hou; Chenlong Liu; Peng Su; Jun Ma; Tao Yang (Water Research, 2024)

Amorphous Fe substrate enhances nitrogen and phosphorus removal in sulfur autotrophic process - Kebing Zhou; Hao Zhang; Dong Guo; Shuocheng Gao; Yuansheng Pei; Li'an Hou (Water Research, 2024)

Treatment of emerging pyrrolizidine alkaloids in drinking water by UV/persulfate process: Kinetics, energy efficiency and degradation pathway - Menghong Gao; Shuili Yu; Li'an Hou; Xingli Ji; Rongsheng Ning; Ying Xu; Lei Li (Chemical Engineering Journal, 2024)

Understanding the dilemmas and breakdown of the reactive migration of in situ groundwater injection reagents from an environmental geology perspective - Peng Wang; Jia Li; Pei An; Bingrui Yang; Deyi Hou; Shengyan Pu (Critical Reviews in Environmental Science and Technology, 2024)

Deciphering the removal of antibiotics and the antibiotic resistome from typical hospital wastewater treatment systems - Dahai He; Jiang Li; Weihai Yu; Yingyuan Zhang; Bin Wang; Tao Wang; Huaikai Yang; Yuntao Zhang; Weijie Chen; Yancheng Li; Faming Feng; Li-An Hou (Science of The Total Environment, 2024)

Preferentially in-situ generated copper nanograins boosting fast kinetic conversion magnesium storage of bimetallic copper-cobalt sulfide cathode - Yaping Xia; Chunxiao Chen; Lin Ran; Hou-an Zhang; Shuai Cui; Panfei Xiao; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2024)

Assessing radiometric calibration methods for multispectral UAV imagery and the influence of illumination, flight altitude and flight time on reflectance, vegetation index and inversion of winter wheat AGB and LAI - Honglei Zhu; Yanwei Huang; Zhaokang An; Han Zhang; Yongyue Han; Zihui Zhao; Feifan Li; Chan Zhang; Cuicui Hou (Computers and Electronics in Agriculture, 2024)

Functionalization of seawater reverse osmosis membrane with quorum sensing inhibitor to regulate microbial community and mitigate membrane biofouling - Chao Chen; Yu Yang; Chung-Hak Lee; Satoshi Takizawa; Zhenghua Zhang; How Yong Ng; Li-an Hou (Water Research, 2024)

Response of microbial communities to the changes in grazing intensity and season in a typical steppe - Muhammad Usman; Lan Li; Mengyuan Wang; Zhen Wang; An Hu; Liyuan Shi; Fujiang Hou (Environmental Research, 2024)

Active dark carbon fixation evidenced by 14C isotope assimilation and metagenomic data across the estuarine-coastal continuum - Bolin Liu; Yanling Zheng; Xinyu Wang; Lin Qi; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Science of The Total Environment, 2024)

Generation of •OH and intermediate manganese species for the efficient removal of micropollutants via photocatalysis of permanganate by indium oxide - Juan Li; Maoju Jiang; Peng Su; Qixiao Lv; Linqian An; Ge Zeng; Xiangyang Hou; Wenqi Li; Chunzhao Chen; Jun Ma; Tao Yang (Chemical Engineering Journal, 2024)

A comprehensive evaluation of the temporal and spatial fouling characteristics of RO membranes in a full-scale seawater desalination plant - Chao Chen; Yu Yang; Nigel J.D. Graham; Zhenyu Li; Xingtao Yang; Zhining Wang; Nadia Farhat; Johannes S. Vrouwenvelder; Li-an Hou (Water Research, 2024)

Exfoliated MXene/poly-melamine-formaldehyde composite membranes for removal of heavy metals and organics from aqueous solutions - Tian-Qi Zhang; Shuang Hao; Jun-Kai Zhao; Zhi-Qian Jia; Hong-Wei Tan; Yu Yang; Li-An Hou (Journal of Hazardous Materials, 2024)

Mobile genetic elements affect the dissemination of antibiotic resistance genes (ARGs) of clinical importance in the environment - Ye Li; Ruilin Li; Jie Hou; Xuan Sun; Yajun Wang; Linyun Li; Fengxia Yang; Yanpo Yao; Yi An (Environmental Research, 2024)

Efficient degradation of carbamazepine by sulfate doped LDO/CN in the photo-assisted peroxymonosulfate system - Kexuan Gao; Doudou Huang; Li-an Hou; Xiaoqiang An; Satoshi Takizawa; Yu Yang (Chemical Engineering Journal, 2024)

Insights into biomass mild gasification based on mass-energy balance: Establishing condition, thermodynamic mechanisms, and product properties - Xuemei Fu; Jian Li; Beibei Yan; Guanyi Chen; Li'an Hou; Junyu Tao (Chemical Engineering Journal, 2024)

Coupling electrokinetic technique with hydrothermal carbonization for phosphorus-enriched hydrochar production and heavy metal separation from sewage sludge - Xutong Wang; Ondřej Mašek; Huwei Li; Fan Yu; Christian Wurzer; Junxia Wang; Beibei Yan; Xiaoqiang Cui; Guanyi Chen; Li'an Hou (Chemical Engineering Journal, 2024)

Drivers and impacts of decreasing concentrations of atmospheric volatile organic compounds (VOCs) in Beijing during 2016–2020 - Yafei Liu; Shijie Yin; Siqing Zhang; Wei Ma; Xin Zhang; Peipei Qiu; Chenlu Li; Guangpeng Wang; Dongli Hou; Xiang Zhang; Junling An; Yele Sun; et al. (Science of The Total Environment, 2024)

Erythromycin fermentation residue exposure induces a short-term wave of antibiotic resistance in a soil-lettuce system - Jieya Zhou; Hao Wu; Zongru Wu; Lihu Shi; Yunpeng Shen; Shulei Tian; Li-an Hou (Science of The Total Environment, 2023)

Modification of the distribution of humic acid complexations by introducing microbubbles to membrane distillation process for effective membrane fouling alleviation - Xitong Wang; Pan Li; Yubing Ye; Chen'ao Xu; Yanling Liu; Enchao Li; Qing Xia; Li'an Hou; Shuili Yu (Journal of Environmental Management, 2023)

Long-term grazing improved soil chemical properties and benefited community traits under climatic influence in an alpine typical steppe - Yu-Wen Zhang; Ze-Chen Peng; Sheng-Hua Chang; Zhao-Feng Wang; Duo-Cai Li; Yu-Feng An; Fu-Jiang Hou; Ji-Zhou Ren (Journal of Environmental Management, 2023)

Corrigendum to “Effects of pollen concentration on allergic rhinitis in children: A retrospective study from Beijing, a Chinese megacity” [Environ. Res. 229(2023) 115903/ER-22-11024] - Yuxin Zhao; Zhaobin Sun; Li Xiang; Xingqin An; Xiaoling Hou; Jing Shang; Ling Han; Caihua Ye (Environmental Research, 2023)

In-situ generated elemental selenium nanograins cooperated with NiSe2 microspheres for significantly enhanced magnesium-storage performance - Changchun Hu; Lin Ran; Hou-an Zhang; Shuai Cui; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2023)

Long-Term Plant Community Removal Alters Soil Nematode Communities Mainly Through the Trophic Cascading Effects of Fungal Channel - Hongxian Song; Xiao Hou; Hanwen Cui; Sa Xiao; Ziyang Liu; Jingwei Chen; Jiajia Wang; Anning Zhang; Xin Li; Yajun Wang; Zi Yang; Kun Liu; et al. (Journal of Soil Science and Plant Nutrition, 2023)

Tidal dynamics regulates potential coupling of carbon‑nitrogen‑sulfur cycling microbes in intertidal flats - Yuhui Niu; Zhirui An; Dengzhou Gao; Feiyang Chen; Jie Zhou; Bolin Liu; Lin Qi; Li Wu; Zhuke Lin; Guoyu Yin; Xia Liang; Hongpo Dong; et al. (Science of The Total Environment, 2023)

A review on polyhydroxyalkanoates production from various organic waste streams: Feedstocks, strains, and production strategy - Xuemei Fu; Heng Xu; Qi Zhang; Jiaxing Xi; Huihui Zhang; Mingxia Zheng; Beidou Xi; Li'an Hou (Resources, Conservation and Recycling, 2023)

Wet torrefaction coupled pyrolysis of camel dung: Fuel properties, pyrolysis behaviors and evolved gases - Yanshan Wang; Xiaochao Zhu; Songjiang Li; Yingjin Song; Guanyi Chen; Li'an Hou (Fuel, 2023)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Effects of microplastics on denitrification and associated N2O emission in estuarine and coastal sediments: insights from interactions between sulfate reducers and denitrifiers - Cheng Chen; Guoyu Yin; Qiuxuan Li; Youran Gu; Dongyao Sun; Soonmo An; Xia Liang; Xiaofei Li; Yanling Zheng; Lijun Hou; Min Liu (Water Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

A biomimetic nanoreactor for combinational chemo/chemodynamic therapy of choriocarcinoma through synergistic apoptosis and ferroptosis strategy - Hui Yu; Haoyi Zhao; Yujie Zhang; Yuemin Hou; Runqing Li; Ting Liang; Yuanyuan Zhang; Cheng Li; Jingjie Zhao; Mingzhen Zhang; Ruifang An (Chemical Engineering Journal, 2023)

Conversion and impact of dissolved organic matters in a heterogeneous catalytic peroxymonosulfate system for pollutant degradation - Yanshan Wang; Ning Li; Qinglong Fu; Zhanjun Cheng; Yingjin Song; Beibei Yan; Guanyi Chen; Li'an Hou; Shaobin Wang (Water Research, 2023)

ZmMS1/ZmLBD30-orchestrated transcriptional regulatory networks precisely control pollen exine development - Quancan Hou; Xueli An; Biao Ma; Suowei Wu; Xun Wei; Tingwei Yan; Yan Zhou; Taotao Zhu; Ke Xie; Danfeng Zhang; Ziwen Li; Lina Zhao; et al. (Molecular Plant, 2023)

Construction of Bi2MoO6/CoWO4 Z-scheme heterojunction for high-efficiency photocatalytic degradation of norfloxacin under visible light: Performance and mechanism insights - Huaikai Yang; Jiang Li; Qi Su; Bin Wang; Zichun Zhang; Yongheng Dai; Yancheng Li; Li'an Hou (Chemical Engineering Journal, 2023)

Characteristics of mesenchymal stem cells and their exosomes derived from giant panda (Ailuropoda melanoleuca) endometrium - Yu-Liang Liu; Jia-Song Chen; Jun-Hui An; Zhi-Gang Cai; Jing-Chao Lan; Yuan Li; Xiang-Wei Kong; Ming-Yue Zhang; Rong Hou; Dong-Hui Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Degradation performance and bioinformatic analysis of graphite electrode electrolysis cells for erythromycin fermentation residue - Jieya Zhou; Zongru Wu; Shuai Wang; Hao Wu; Lihu Shi; Shulei Tian; Li-an Hou (Journal of Cleaner Production, 2023)

Effects of pollen concentration on allergic rhinitis in children: A retrospective study from Beijing, a Chinese megacity - Yuxin Zhao; Zhaobin Sun; Li Xiang; Xingqin An; Xiaoling Hou; Jing Shang; Ling Han; Caihua Ye (Environmental Research, 2023)

Potential response of dark carbon fixation to global warming in estuarine and coastal waters - Lin Qi; Yanling Zheng; Lijun Hou; Bolin Liu; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Global Change Biology, 2023)
Dark carbon fixation (DCF), through which chemoautotrophs convert inorganic carbon to organic carbon, is recognized as a vital process of global carbon biogeochemical cycle. However, little is known about the response of DCF processes in estuarine and coastal waters to global warming. Using radiocarbon labelling method, the effects of temperature on the activity of chemoautotrophs were investigated in benthic water of the Yangtze estuarine and coastal areas. A dome‐shaped thermal response pattern was observed for DCF rates (i.e., reduced rates at lower or higher temperatures), with the optimum temperature ( T opt ) varying from about 21.9 to 32.0°C. Offshore sites showed lower T opt values and were more vulnerable to global warming compared with nearshore sites. Based on temperature seasonality of the study area, it was estimated that warming would accelerate DCF rate in winter and spring but inhibit DCF activity in summer and fall. However, at an annual scale, warming showed an overall promoting effect on DCF rates. Metagenomic analysis revealed that the dominant chemoautotrophic carbon fixation pathways in the nearshore area were Calvin‐Benson‐Bassham (CBB) cycle, while the offshore sites were co‐dominated by CBB and 3‐hydroxypropionate/4‐hydroxybutyrate cycles, which may explain the differential temperature response of DCF along the estuarine and coastal gradients. Our findings highlight the importance of incorporating DCF thermal response into biogeochemical models to accurately estimate the carbon sink potential of estuarine and coastal ecosystems in the context of global warming.

Hydroxylation of some emerging disinfection byproducts (DBPs) in water environment: Halogenation induced strong pH-dependency - Zexiu An; Dongchen Yang; Mingxue Li; Yanru Huo; Jinchan Jiang; Yuxin Zhou; Yuhui Ma; Wenlong Hou; Jinlin Zhang; Maoxia He (Journal of Hazardous Materials, 2023)

Salinity variations of the inner Yangtze Sea during the Ordovician-Silurian transition and its influences on marginal marine euxinia - Guangyao Cao; Yu Liu; Chao Li; Ping'an Peng; Mingcai Hou; Gary G. Lash; Xiaolin Zhou; Yuanchun Li; Ying Song (Global and Planetary Change, 2023)

Overlooked impacts of natural organic matter conversion in a Fe(II)-induced peroxymonosulfate activation system for river water remediation - Lan Liang; Guanyi Chen; Jianhui Zhao; Penghui Shao; Ning Li; Mengting He; Qinglong Fu; Beibei Yan; Li-an Hou (Science of The Total Environment, 2023)

Applications of vacancy defect engineering in persulfate activation: Performance and internal mechanism - Ting Zhang; Shuang Wu; Ning Li; Guanyi Chen; Li’an Hou (Journal of Hazardous Materials, 2023)

A novel reutilization of ash from biomass gasification process: Feasibility and products improvement analysis - Qianqian Guo; Beibei Yan; Yanjun Hu; Xiang Guo; Wenzhu Wu; Zhanjun Cheng; Guanyi Chen; Li'an Hou (Fuel, 2023)

Summer O3 pollution cycle characteristics and VOCs sources in a central city of Beijing-Tianjin-Hebei area, China - Yanan Guan; Xuejiao Liu; Zhiyang Zheng; Yanwei Dai; Guimin Du; Jing Han; Li'an Hou; Erhong Duan (Environmental Pollution, 2023)

Petrogenesis and Tectonic Implications of the Late Silurian–Early Devonian Bimodal Intrusive Rocks in the Central Beishan Orogenic Belt, NW China: Constraints by Petrology, Geochemistry and Hf Isotope - Jian Tian; Hou-Tian Xin; Xue-Jian Teng; Min Li; Qun-An Liao; Yong Zhang; Bang-Fang Ren (Journal of Earth Science, 2023)

Grazing weakens N-addition effects on soil greenhouse gas emissions in a semi-arid grassland - Zhen Wang; Xiumin Zhang; Mengyuan Wang; Lan Li; An Hu; Xianjiang Chen; Shenghua Chang; Fujiang Hou (Agricultural and Forest Meteorology, 2023)

Sustainable on-farm strategy for the disposal of antibiotic fermentation residue: Co-benefits for resource recovery and resistance mitigation - Jieya Zhou; Hao Wu; Lihu Shi; Xuming Wang; Yunpeng Shen; Shulei Tian; Li-an Hou (Journal of Hazardous Materials, 2023)

Enhancing the desalination performance of polyamide nanofiltration membranes via in-situ incorporation of zwitterionic nanohydrogel - Lihui Guo; Yuzhang Zhu; Li-an Hou; Dianyu Dong; Aqiang Wang; Yu Yang (Desalination, 2023)

Influence of cadmium and copper mixtures to rhizosphere bacterial communities - Qirui An; Yunyang Li; Na Zheng; Jincai Ma; Shengnan Hou; Siyu Sun; Sujing Wang; Pengyang Li; Xiaoqian Li; Chunmei Zhao (Soil Ecology Letters, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Effects of periodic drying-wetting on microbial dynamics and activity of nitrite/nitrate-dependent anaerobic methane oxidizers in intertidal wetland sediments - Feiyang Chen; Yuhui Niu; Zhirui An; Li Wu; Jie Zhou; Lin Qi; Guoyu Yin; Hongpo Dong; Xiaofei Li; Dengzhou Gao; Min Liu; Yanling Zheng; et al. (Water Research, 2023)

Response of sediment microbial communities to different levels of PAC contamination and exposure time - Xiao Xiao; Ya-Li Zhang; Zi-An Zhou; Fan Wu; Hou-Feng Wang; Xin Zong (Science of The Total Environment, 2023)

Effects of microbial inoculum on microbial community and enzyme activity involved in nitrogen-sulfur metabolism during sewage sludge composting - Tingting Hou; Yujie Zhou; Xu Cao; Weiguang Li; Shumei Zhang; Yi Zhao; Li Chen; Qi An; Liqiang Meng (Science of The Total Environment, 2023)

Temporal and spatial evolutionary trends of regional extreme precipitation under different emission scenarios: Case study of the Jialing River Basin, China - Shanghong Zhang; Wenda Li; Wenjie An; Jun Hou; Xiaoning Hou; Caihong Tang; Zhiguo Gan (Journal of Hydrology, 2023)

A new filterless indoor air purifier for particulate matter and bioaerosol based on heterogeneous condensation - Shijun Yan; Chang Liu; Li-an Hou; Bo Wang; Yumeng Zhang (Environmental Research, 2023)

Correction to: Important revelations of different degrees of COVID‑19 lockdown on improving regional air quality: a case study of Shijiazhuang, China - Yanan Guan; Ying Shen; Xinyue Liu; Xuejiao Liu; Jing Chen; Dong Li; Man Xu; Litao Wang; Erhong Duan; Li’an Hou; Jing Han (Environmental Science and Pollution Research, 2023)

Distribution and migration of antibiotic resistance genes, as well as their correlation with microbial communities in swine farm and its surrounding environments - Bin Wang; Lei Song; Wenjia Li; Li'an Hou; Jiang Li; Xiaoyi Xu; Guishang Sheng (Environmental Pollution, 2023)

All-in-one additive enables defect passivated, crystallization modulated and moisture resisted perovskite films toward efficient solar cells - Chuanming Tian; Yu Zhao; Xuefei Han; Bin Li; Yichuan Rui; Hao Xiong; Yu Qiu; Wei An; Kerui Li; Chengyi Hou; Yaogang Li; Hongzhi Wang; et al. (Chemical Engineering Journal, 2023)

Important revelations of different degrees of COVID-19 lockdown on improving regional air quality: a case study of Shijiazhuang, China - Yanan Guan; Ying Shen; Xinyue Liu; Xuejiao Liu; Jing Chen; Dong Li; Man Xu; Litao Wang; Erhong Duan; Li’an Hou; Jing Han (Environmental Science and Pollution Research, 2022)

Maternal exposure to cooking oil fumes during pregnancy and autistic‐like behaviors in Chinese preschoolers - Jian-Hui Yang; Esben Strodl; Chuan-An Wu; Xiang-Yu Hou; Xiao-Na Yin; Guo-Min Wen; Deng-Li Sun; Dan-Xia Xian; Jing-Yi Chen; Ying-Jie Chen; Jing Chen; Wei-Qing Chen (Environmental Science and Pollution Research, 2022)

Acute effects of black carbon on mortality in nine megacities of China, 2008–2016: a time-stratified case-crossover study - Yi Li; Canjun Zheng; Xingqin An; Qing Hou (Environmental Science and Pollution Research, 2022)

Geochemical characteristics and growth suitability assessment of Scutellaria baicalensis Georgi in the Earth’s critical zone of North China - Xia Li; Xiao-feng Wei; Jin Wu; Zhi-qiang Yin; Li-qin Wan; Hou-yun Sun; Yong-long An (Journal of Mountain Science, 2022)

The establishment of giant panda (Ailuropoda melanoleuca) fibroblast cell line - Yuliang Liu; Jiasong Chen; Tongying Feng; Rong Hou; Zhigang Cai; Donghui Wang; Mingyue Zhang; Yuan Li; Yijiao Chen; Junhui An (In Vitro Cellular & Developmental Biology - Animal, 2022)

MicroRNAs sequencing of plasma exosomes derived from patients with atrial fibrillation: miR-124-3p promotes cardiac fibroblast activation and proliferation by regulating AXIN1 - Pengju Zhu; Huilin Li; An Zhang; Zhan Li; Yong Zhang; Manyi Ren; Yujiao Zhang; Yinglong Hou (Journal of Physiology and Biochemistry, 2022)

Lignin Synthesis Related Genes with Potential Significance in the Response of Upland Cotton to Fusarium Wilt Identified by Transcriptome Profiling - Jianan Hou; Fu’an Zhao; Xiaojie Yang; Wu Li; Deyi Xie; Zhongjie Tang; Shuping Lv; Lihong Nie; Yao Sun; Mengmeng Wang; Yajing Zhu; Xiaopei Bo; et al. (Tropical Plant Biology, 2021)
Fusarium wilt, caused by the fungus Fusarium oxysporum Schlecht. f. sp. vasinfectum (Fov) is a destructive soil-borne cotton disease. To profile the genes and pathways responding to Fov infection, we compared transcriptomic responses before and after F. oxysporum inoculation in a highly resistant cotton cultivar, Yumian21, and a highly susceptible cultivar, Jimian11. Although the overall gene expression pattern was downregulated in both cultivars, the global gene expression in the resistant cultivar was stronger than that in the susceptible cultivar. In addition, the expressed genes of two cultivars mostly differed in “cellular process,” “single-organism process,” “metabolic process,” and “response to stimulus” functional groups in the biological process Gene Ontology category: the upregulated differentially expressed genes (DEG) were largely enriched in the resistant cultivar, while the downregulated DEGs were largely enriched in the susceptible cultivar. Phenylpropanoid biosynthesis and phenylalanine metabolism are the key metabolic pathways in cotton in response to Fov. We found that lignin plays a potential role in cotton resistance to Fov. Two coding genes, caffeic acid 3-O-methyltransferase and peroxidase2 , as well as the two transcription factors MYB46 and MYB86 , are possibly involved in the accumulation and synthesis of lignin. Furthermore, the result showed that the quantification of lignin could be potentially used as a selection tool to identify Fusarium wilt resistant cotton.

Isolation, culture, and characterization of cells derived from giant panda (Ailuropoda melanoleuca) semen - Yuliang Liu; Yuan Li; Rong Hou; Zhigang Cai; Donghui Wang; Jiasong Chen; Feiping Li; Yijiao Chen; Junhui An (In Vitro Cellular & Developmental Biology - Animal, 2021)

Temporal variation of airborne fungi in university library rooms and its relation to environmental parameters and potential confounders - Dingmeng Wu; Ying Zhang; Chenbo Zhao; Angui Li; Li’an Hou; Yu Tian; Jing Xiong; Ran Gao (Environmental Science and Pollution Research, 2021)

The regulation of dermal mesenchymal stem cells on keratinocytes apoptosis - Peng An; Jianxiao Xing; Aihong Peng; Xincheng Zhao; Wenjuan Chang; Nannan Liang; Yue Cao; Juan Li; Junqin Li; Ruixia Hou; Xinhua Li; Kaiming Zhang (Cell and Tissue Banking, 2021)

Effects of Sulfamethoxazole Exposure on the Growth, Antioxidant System of Chlorella vulgaris and Microcystis aeruginosa - Xiaotong Dong; Shaohua Sun; Ruibao Jia; Lirong Xu; Wei Hou; Nannan Lu; Mingquan Wang; Qinghua Zhao; Li’an Hou (Bulletin of Environmental Contamination and Toxicology, 2020)

Study on the removal of humic acid by ultraviolet/persulfate advanced oxidation technology - Guangxue Ji; Shaohua Sun; Ruibao Jia; Jianguang Liu; Zhenxing Yao; Mingquan Wang; Qinghua Zhao; Li’an Hou (Environmental Science and Pollution Research, 2020)

The isolation and culture of giant panda (Ailuropoda melanoleuca) breast milk cells - Chen Yijiao; Wang Donghui; Liu Yuliang; Li Feiping; He Ping; Cai Zhigang; Zhang Hao; Chen Min; Hou Rong; An Junhui (In Vitro Cellular & Developmental Biology - Animal, 2020)

Lignite-Activated Carbon Grafted PAA Combined with Conventional Drinking Water Treatment Processes for the Emergency Removal of Trace Pb(II) Pollution - Lihua Dong; Shujie Pan; Zhansheng Wang; Li’an Hou; G. Zhou; Guanyi Chen (Water, Air, & Soil Pollution, 2020)

Impacts of biofouling on the removal of pharmaceutically active compounds by a nanofiltration membrane - Yu Yang; Chen Li; Li-an Hou (Environmental Science and Pollution Research, 2019)

Genome-wide analysis of maize GPAT gene family and cytological characterization and breeding application of ZmMs33/ZmGPAT6 gene - Taotao Zhu; Suowei Wu; Danfeng Zhang; Ziwen Li; Ke Xie; Xueli An; Biao Ma; Quancan Hou; Zhenying Dong; Youhui Tian; Jinping Li; Xiangyuan Wan (Theoretical and Applied Genetics, 2019)

Non-coding RNAs and transposable elements in plant genomes: emergence, regulatory mechanisms and roles in plant development and stress responses - Jinna Hou; Dandan Lu; Annaliese S. Mason; Baoquan Li; Meili Xiao; Sufang An; Donghui Fu (Planta, 2019)

Comparative analysis of molecular activity in dermal mesenchymal stem cells from different passages - Xinhua Li; Junqin Li; Xincheng Zhao; Qiang Wang; Xiaohong Yang; Yueai Cheng; Min Zhou; Gang Wang; Erle Dang; Xiaoli Yang; Ruixia Hou; Peng An; et al. (Cell and Tissue Banking, 2018)

Reversible immortalization of sheep fetal fibroblast cells by tetracycline-inducible expression of human telomerase reverse transcriptase - Na Zhang; Jianwei Li; Xia Zhong; Xiaorong An; Jian Hou (Biotechnology Letters, 2016)

Sodium butyrate-induced histone hyperacetylation up-regulating WT1 expression in porcine kidney fibroblasts - Wentao Tan; Yue Chen; Peipei An; Aibing Wang; Meiran Chu; Liuxin Shi; Xiaoxiao Hou; Bo Tang; Xueming Zhang; Ziyi Li (Biotechnology Letters, 2015)

Biological characteristics of rat dorsal root ganglion cell and human vascular endothelial cell in mono- and co-culture - Quan Yuan; Jian-Jun Li; Chun-Hou An; Li Sun (Molecular Biology Reports, 2014)

Comparison between conidia and blastospores of Esteya vermicola, an endoparasitic fungus of the pinewood nematode, Bursaphelenchus xylophilus - Yun-Bo Wang; Zhi-Hong Yang; Jiao-Jiao Yu; Yong-An Zhang; Jian-Jie Xue; Zheng Li; Jing-Jie Li; Chun-Yan Wang; Zhen Wang; Jin-Gang Hou; Shahraz Begum; Li-Juan Gu; et al. (World Journal of Microbiology and Biotechnology, 2013)

Paracoccus siganidrum sp. nov., isolated from fish gastrointestinal tract - Ying Liu; Qing-yi Xie; Kui Hong; Lei Li; Ya-mei Zhao; Yi-li Tang; Jun-ying An; Ping-ping Zhu; Chun-hou Xu (Antonie van Leeuwenhoek, 2013)

Novel polymorphisms of goat growth hormone and growth hormone receptor genes and their effects on growth traits - Xiaopeng An; Lixin Wang; Jinxing Hou; Guang Li; Yuxuan Song; Jiangang Wang; Mingming Yang; Yihong Cui; Binyun Cao (Molecular Biology Reports, 2011)

Study on polymerization effect of polyembryony genes by SSCP marker and family trees in Chinese goats - Guang Li; Xiaopeng An; Jinxing Hou; Ling Li; Dan Han; Mingming Yang; Yana Wang; Guangqin Zhu; Jiangang Wang; Yuxuan Song; Bin Yun Cao (Molecular Biology Reports, 2011)

A Sabin 2-related poliovirus recombinant contains a homologous sequence of human enterovirus species C in the viral polymerase coding region - Yong Zhang; Fan Zhang; Shuangli Zhu; Li Chen; Dongmei Yan; Dongyan Wang; Ruiyan Tang; Hui Zhu; Xiaohui Hou; Hongqiu An; Hong Zhang; Wenbo Xu (Archives of Virology, 2010)

Study of Antibacterial Activity of ZnZnbisporphyrin Complexes and its Free Components on Staphylococcus aureus by Microcalorimetry - Xiang-jiao Xu; Chun-qiao Chen; Zhuo-yuan Wang; Yi Zhang; An-xin Hou; Chao-Hong Li; Yi Liu (Biological Trace Element Research, 2009)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

Cloning and characterization of a novel albinism-related zinc finger protein gene in Japanese flounder - Jiaqing Wang; Lin Hou; Xiangyang Zou; Feng Yao; Xiaoyan Li; Xintao Zhao; Ruifeng Zhang; Lijuan Jiang; Wenjing Sun; Jialu An (Fish Physiology and Biochemistry, 2007)

Chemical Modification of Insulin by N-phosphorylation - Yan Liu; Peng-xiang Xu; Jian-bo Hou; Li-feng Yang; Jin-an Chen; Yu-fen Zhao (International Journal of Peptide Research and Therapeutics, 2005)

Development of Indicators Within Different Policy Contexts for Endemic Arsenic Impacts in the People's Republic of China - Peter J. Peterson; W. Peter Williams; Linsheng Yang; Wuyi Wang; Shaofan Hou; Ribang Li; Jian'an Tan (Environmental Geochemistry and Health, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)